Cancer outcomes of pregnancy after diagnosis of breast cancer in premenopausal women: an updated systematic review and meta-analysis - Mei, Heting; Song, Qingya; Lu, Wenping; Wang, Xiyue; Liu, Jiaxin; Zhang, Weijia; Chang, Lei; Zhuo, Zhili (Frontiers in Oncology, 2025)
IntroductionBreast cancer is a type of hormone-driven cancer, and pregnancy may increase the risk of recurrence in patients due to hormone surge. Our study was designed to explore the cancer outcomes of premenopausal women who had primary breast cancer and who became pregnant at any time after diagnosis.MethodsSearches were conducted in ten databases until July 2024, with no language restrictions. We analyzed aggregate data across all study populations and performed subgroup analyses by stage, estrogen receptor status, BRCA mutation status, HER2 status, previous treatment, lymph node status, interval between pregnancy and diagnosis, pregnancy type, reproductive status, and breastfeeding status.ResultsFifty-two studies were included. The pregnancy group had longer overall survival (n = 18) [RR = 1.09 (1.06, 1.12), P < 0.001]. Nine studies reported the same results [HR = 0.60 (0.48, 0.73), P < 0.001]. The disease-free survival (n = 7) of the pregnancy group was not significantly longer [HR = 0.90 (0.79, 1.02), P = 0.111]. The pregnancy group had longer breast cancer-specific survival (n = 3) [HR = 0.55 (0.40, 0.76), P < 0.001]. The pregnancy group had a lower recurrence rate (n = 17) [RR = 0.61 (0.55, 0.68), P < 0.001]. The pregnancy group had a higher loco-regional recurrence rate, although the difference was not statistically significant (n = 4) [RR = 1.04 (0.74, 1.47), P = 0.814]. The pregnancy group had a lower distant recurrence rate (n = 5) [RR = 0.50 (0.37, 0.68), P < 0.001]. The pregnancy group had a higher contralateral breast cancer rate, although the difference was not statistically significant (n = 3) [RR = 1.06 (0.76, 1.48), P = 0.742].DiscussionOur findings indicate that pregnancy after breast cancer does not lead to adverse cancer outcomes. Stage, estrogen receptor status, therapy choice (hormone, chemotherapy, or endocrine therapy combined with chemotherapy), and reproductive status are not associated with overall survival. BRCA2 mutation may negatively affect disease-free survival in pregnant patients with breast cancer.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024499971.